THE IMPACT OF TMIP-BASED WEB IN TEACHING TOEFL ON STUDENTS' TOEFL SCORES - Nusi, Ahmad; Zaim, M; Yelliza, Yelliza (TELL - US JOURNAL, 2024)
The study conducted at the Practical Language Learning Center (PLLC) aimed to compare the effectiveness of two teaching methods for TOEFL preparation: the TMIP-Based Web in Teaching TOEFL method and a conventional approach or no specific intervention. A total of 58 students participated, with 25 assigned to the control class and 33 to the experimental class. TOEFL scores served as the measure of learning outcomes. Prior to analysis, Levene's test was used to assess variance equality between groups, followed by an independent samples t-test to compare mean scores. Results revealed a significant difference in mean TOEFL scores between the control (M = 66.96) and experimental (M = 81.58) groups, indicating superior performance in the experimental group. Statistical analyses, supported by SPSS output, affirmed the positive impact of the TMIP-Based Web in Teaching TOEFL method on students' TOEFL scores. The analysis of the SPSS output reveals a significant finding, where the obtained significance value (2-tailed) of 0.000 is considerably less than the conventional threshold of 0.01. This result prompts the rejection of the null hypothesis (Ho) and the acceptance of the alternative hypothesis (H1), indicating a substantial relationship between the TMIP-Based Web in Teaching TOEFL method and students' TOEFL scores. Furthermore, this conclusion is reinforced by both manual t-test analysis and SPSS assistance, both of which corroborate a statistically significant impact of the teaching method on students' TOEFL scores.